2020 IEEE International Conference on Artificial Intelligence and Virtual Reality (AIVR) 2020
DOI: 10.1109/aivr50618.2020.00072
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Deep Learning Approaches to EEG-Based Classification of Cybersickness in Virtual Reality

Abstract: Cybersickness is an unpleasant side effect of exposure to a virtual reality (VR) experience and refers to such physiological repercussions as nausea and dizziness triggered in response to VR exposure. Given the debilitating effect of cybersickness on the user experience in VR, academic interest in the automatic detection of cybersickness from physiological measurements has crested in recent years. Electroencephalography (EEG) has been extensively used to capture changes in electrical activity in the brain and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Simulation sickness is the term used to describe the temporary side effects caused by immersive VR, which may include symptoms such as nausea, dizziness or eyestrain. (Yildirim, 2020 ). Experienced simulation sickness may affect users' interest in using VR products (Davis et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Simulation sickness is the term used to describe the temporary side effects caused by immersive VR, which may include symptoms such as nausea, dizziness or eyestrain. (Yildirim, 2020 ). Experienced simulation sickness may affect users' interest in using VR products (Davis et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…It incorporates convolutional layers that perform convolutions to identify patterns, pooling layers for faster parameterization, and fullyconnected layers with full connections to the previous layer for high-level reasoning [71]. Given the high performance of CNN architectures for image data, using images extracted by sequential raw EEG data as an input to a CNN constitutes a trend in EEG preprocessing [34], [75]. These images are called topo-maps and preserve the spatial and spectral traits of the signal, namely, the electrode location and adequate frequency information [76].…”
Section: D: Deep Learningmentioning
confidence: 99%
“…Our review shows that including physiological data for training results does not ensure high prediction power. However, Yildirim's review (Yildirim 2020) reported that EEG signals showed a great power for successful prediction. The difference may lie in the sample size or the content used.…”
Section: Prediction Of Cybersicknessmentioning
confidence: 99%